Problem Solving for Wireless Sensor Networks - García-Hernando, Ana-Belén.; Martínez-Ortega, José-Fernán.; López-Navarro, Juan-Manuel.; Prayati, Aggeliki; Redondo-López, Luis.; SpringerLink (Online service) (London : Springer London : Imprint: Springer, 2008)
Wireless Sensor Networks (WSN) is an area of huge research interest, attracting substantial attention from industry and academia for its enormous potential and its inherent challenges. This book delivers a comprehensive review of the state-of-the-art related to the most important technological issues in WSN. This wide-ranging, reader-friendly text covers topics such as hardware platforms, radio technologies, software technologies (including middleware), and network and deployment aspects. It discusses the main open issues inside each of these categories, and in it identifies innovations considered most interesting for future research. Features: • Comprehensive overview of the state-of-the-art of WSN, from hardware to applications • Includes survey of commercial products and solutions, European projects and research papers • Identifies the main open issues and innovations • Covers standards and safety regulation for WSN • Analyses several WSN application scenarios at both utility and technical levels • Highlights the major difficulties that can arise when using WSN technologies • Organised into self-contained chapters, allowing readers to focus on their specific interests Complete, cutting-edge and resulting from the work of many reknown researchers, this book is an invaluable reference guide for graduate students, researchers, and practitioners who want to grasp the main technological and research challenges that drive the design and deployment of a WSN solution.
Radio-Frequency Technologies for WSNs -- Hardware Platforms for WSNs -- Software Technologies in WSNs -- Network Aspects and Deployment in WSNs -- Standards and Safety Regulations for WSNs -- European Research Projects Related to WSNs -- WSN Application Scenarios.
Keywords: Computer communication systems; Computer Communication Networks